2008 IEEE International Symposium on Information Theory 2008
DOI: 10.1109/isit.2008.4595178
|View full text |Cite
|
Sign up to set email alerts
|

Finite signal-set capacity of two-user Gaussian Multiple Access Channel

Abstract: Abstract-The capacity region of a two-user Gaussian Multiple Access Channel (GMAC) with complex finite input alphabets and continuous output alphabet is studied. When both the users are equipped with the same code alphabet, it is shown that, rotation of one of the user's alphabets by an appropriate angle can make the new pair of alphabets not only uniquely decodable, but will result in enlargement of the capacity region. For this set-up, we identify the primary problem to be finding appropriate angle(s) of rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 7 publications
(2 reference statements)
0
54
0
Order By: Relevance
“…With finite input alphabets and an unquantized receiver, the two-user Gaussian MAC rate region has been studied in [5]. In [5], in terms of the achievable rate region, it was shown that, compared to having both the users transmit using the same finite signal set, it is better to have the second user transmit using a rotated version of the first user's signal set.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…With finite input alphabets and an unquantized receiver, the two-user Gaussian MAC rate region has been studied in [5]. In [5], in terms of the achievable rate region, it was shown that, compared to having both the users transmit using the same finite signal set, it is better to have the second user transmit using a rotated version of the first user's signal set.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], in terms of the achievable rate region, it was shown that, compared to having both the users transmit using the same finite signal set, it is better to have the second user transmit using a rotated version of the first user's signal set. We refer to the two-user Gaussian MAC system model in [5] (with finite input alphabet and no output quantization) as constellation constrained MAC (CCMAC).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations